Virtual group consultations offer continuity of care globally during Covid‐19. Issue 2 (20th December 2020) - Birrell, Fraser; Lawson, Rob; Sumego, Marianne; Lewis, Jessica; Harden, Angela; Taveira, Tracey; Stevens, John; Manson, Alison; Pepper, Linda; Ickovics, Jeannette
Abstract: Covid‐19 has led to virtual care (mainly telephone consultations) becoming a default worldwide, despite well‐documented shortcomings. Published evidence on virtual group consultations is limited, although interest and front‐line experience have grown substantially since pandemic onset. Unpublished data are summarised showing feasibility of transitioning care to this model across different countries, care settings and conditions. An international webinar series has supported development and sharing of best practice and representative data on spread and utilisation of virtual groups. This model of care creates time and space for more questions and answers, so once engaged patients become staunch advocates. Group care supports personalised care and lifestyle medicine, which is growing very rapidly. In the current context, even healthcare providers under pressure can implement virtual group consultations. Most virtual group consultations have a facilitator, so this allows roles to be extended and support education of both students and new team members. These can confer greater access, continuity of care, peer support and timely information about Covid‐19 and may result in better health outcomes. Given the rapid and widespread implementation of virtual care during this pandemic, data should be shared effectively and methodologically sound observational studies and clinical trials to test safety and effectiveness should be promoted now.